If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -9 + 6x = 9 + -15 Reorder the terms: -9 + 2x + 6x = 9 + -15 Combine like terms: 2x + 6x = 8x -9 + 8x = 9 + -15 Combine like terms: 9 + -15 = -6 -9 + 8x = -6 Solving -9 + 8x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 8x = -6 + 9 Combine like terms: -9 + 9 = 0 0 + 8x = -6 + 9 8x = -6 + 9 Combine like terms: -6 + 9 = 3 8x = 3 Divide each side by '8'. x = 0.375 Simplifying x = 0.375
| 4x+13=3+6x-6 | | -4r=5.8r-9.8r | | (2i)(6-8i)= | | 2x(y-3)+7x=14 | | -4-8=4x+3-3x | | -.75(2X+1)=3(x+4)+4 | | 3x+1+15=2x+4(x+1) | | 0.2w-2.46=0.4w | | z+39=17 | | 3x-12+6x+12=8x+17 | | .67h-.33h+11=8 | | 3=-x-5 | | -15+2m=2m | | 5(4x-3)+9=-5 | | 2/3+3m/5=-31/5 | | -9.9h+10.52=-8.28-9.9h+18.8 | | 2x+3(4-5+5)=6-6+7 | | ln(9x+10)-ln(x)=ln(10) | | 14-(9t-2)=-t+30 | | -3(-c-18)=-3-18 | | (5x+10)+58=(11x+2) | | 9x^2-25x+16=0 | | 8x^2-28X+24=0 | | .5t-3t+5=0 | | 52+x=2(27+x) | | 0.8b-3.4b+15.61=-13.39-2.6b | | 48=8x+2 | | 6x+7x-36=90-5x | | 4(x+2)=2(2x+5)-2 | | 9.22-2.2t=-2.2t+9.22 | | 5(7-2x)=-55 | | (3i)(-5i)= |